Kajian literatur: Integrasi tpack dalam manajemen kurikulum pendidikan dan dampaknya terhadap kualitas pengajaran melalui teknologi - Muallim (Journal of Profession Education, 2025)
This study examines the integration of Technological Pedagogical Content Knowledge (TPACK) into curriculum management in education through a Systematic Literature Review (SLR) approach. It aims to map how TPACK is implemented at both classroom and curriculum levels, its impact on teaching quality and learning outcomes, and the remaining research gaps. Articles were sourced from Google Scholar (2020–2025) using keywords related to TPACK, its integration, and curriculum management, then selected based on relevance, peer‑reviewed status, and methodological quality. The findings show that TPACK is generally implemented through lesson plan/module design, the selection of digital media aligned with objectives and content, and student‑centered interactive learning activities. TPACK integration is reported to enhance engagement, learning outcomes, and higher‑order thinking skills, and to support scope and sequence mapping and technology‑based curriculum development. However, limited infrastructure, teacher training, policy support, and the scarcity of longitudinal studies in developing‑country contexts remain key obstacles, underscoring the need for further research and stronger TPACK‑based curriculum policies.